Analisis Etis Penggunaan Rekayasa Genetik pada Bidang Kesehatan - Hia, Jun Mestika Fati; Gulo, Denika; Hulu, Lisna Dewita; Zebua, Abertina; Ndraha, Fita Kritiani; Zega, Novelina Andriani (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The rapid advancement of modern biotechnology has brought fundamental changes to the field of healthcare, particularly through the application of genetic engineering, gene therapy, and genome-editing technologies such as CRISPR-Cas9. These innovations have opened significant opportunities for the prevention, diagnosis, and treatment of various genetic and degenerative diseases that were previously difficult to manage. Nevertheless, this progress has also generated serious challenges in the realm of bioethics, especially concerning patient safety, the limits of human intervention in life processes, the equitable distribution of technology, and the protection of human rights and dignity. This study aims to analyze the application of healthcare biotechnology from a bioethical perspective by emphasizing the relationship between scientific benefits and moral responsibility. The research method employed is a systematic literature review of scientific journals, bioethics textbooks, and relevant international policy documents. The analysis is conducted based on the four core principles of bioethics, namely beneficence, non-maleficence, autonomy, and justice. The findings indicate that healthcare biotechnology provides significant benefits in improving quality of life and the effectiveness of medical therapies; however, it also entails biological and social risks that cannot be overlooked. These risks include potential long-term effects that are not yet fully understood, the possibility of misuse of technology for non-medical purposes, and unequal access among different social groups. Therefore, the integration of bioethical principles into the research, development, and application of biotechnology is an urgent necessity to ensure that scientific progress advances in harmony with human values, social justice, and the sustainability of healthcare systems.